1992
DOI: 10.1038/bjc.1992.163
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive factors and risk of thyroid cancer. A prospective study of 63,090 women from Norway

Abstract: Summary This prospective study of 63,090 Norwegian women with 124 cases of thyroid cancer diagnosed during 1961 -1989 (McTiernan et al., 1984;Ron et al., 1987;Preston-Martin et al., 1987;Franceschi et al., 1990a). In autopsy studies, no significant sex and age contrasts in the frequency of occult microcarcinomas seem to be present (Fukunaga & Yatani, 1975) On the basis of the total number of cases included in any particular analysis, the expected number was found for each level of the study variable, assumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(36 citation statements)
references
References 14 publications
6
30
0
Order By: Relevance
“…In agreement with our results, a study among 63,090 Norwegian women revealed no strong associations with reproductive factors. 38 The lack of association with reproductive factors is also consistent with a report among Los Angeles County women 39 and with pooled analyses of case-control studies of thyroid cancer. 40,41 However, some modest associations have also been reported, including bilateral oophorectomy, 39 early first childbirth (before age 20 or Ͻ5 years after menarche), artificial menopause 42 and miscarriage as outcome of first pregnancy.…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with our results, a study among 63,090 Norwegian women revealed no strong associations with reproductive factors. 38 The lack of association with reproductive factors is also consistent with a report among Los Angeles County women 39 and with pooled analyses of case-control studies of thyroid cancer. 40,41 However, some modest associations have also been reported, including bilateral oophorectomy, 39 early first childbirth (before age 20 or Ͻ5 years after menarche), artificial menopause 42 and miscarriage as outcome of first pregnancy.…”
Section: Discussionsupporting
confidence: 85%
“…29,38,39,41 Moreover, a decreased risk was found in a study from Italy for women who had ever experienced an abortion (RR ϭ 0.6; 95% CI: 0.4 -1.0). 25 Our data showed an inverse relationship between miscarriage and risk of thyroid cancer, particularly for women who had a miscarriage as outcome of first pregnancy and for those who have had Ն3 miscarriages; there was also a significant trend in decreasing risk with increasing number of miscarriages.…”
Section: Discussionmentioning
confidence: 97%
“…28 A positive association, of similar magnitude, with late last birth (Ն35 years) was also demonstrated in a prospective cohort study of 63,090 women in Norway. 29 Among the various reproductive factors, parity has received most attention. Most case-control studies have demonstrated that women with thyroid cancer have had relatively more pregnancies or live births than controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is known that exposure to ionizing radiation, especially in childhood, increases the risk of developing thyroid cancer (Silverman, 1984;IARC, 2001;Zielinski et al, 2009;Furukawa et al, 2013) However, it is still not clear why thyroid cancer is markedly predominant in females. Previous observational studies on the reproductive system have produced conflicting results (Akslen et al, 1992;Pham et al, 2009;Horn-Ross et al, 2011;Kabat et al, 2012). We, therefore, investigated potential risk factors for thyroid cancer using data from the Khon Kaen Cohort Study, with the main objective of determining the effect of reproductive factors on the occurence of thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%